THE NEW CONCEPT OF DYNAMIC TRANSPORT PLANS (Perner's Contacts, 2014)
The paper deals with a new concept of dynamic transport plan. As we know in the current status not all cities have a key strategic documents for the development of transport. The concept of dynamic plan for responding to any changes in the area, traffic and thus better adapt transport system for requirements in the future.
Keywords: dynamic transport plan; GIS; transport modelling